KEEFEKTIFAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION TERHADAP HASIL BELAJAR MEMBACA INTENSIF SISWA KELAS III SD - Mardhiana, Erly (Widya Wacana: Jurnal Ilmiah, 2018)
AbstractThis research is motivated by the low learning result of intensive reading of students which one of them is caused by less active, creative, and innovative learning process. This study aims to determine the effectiveness of the CIRC model of intensive reading learning outcomes of third grade students of SDN Bogorame Rembang. This research is a quantitative research with Pre-Experimental design with One Group Pretest-Posstest type. The sample technique used is nonprobability sampling with saturated sampling type. Population in this research is all student class III SDN Bogorame Rembang academic year 2017/2018. The result of the research shows that CIRC model is effective toward students' intensive reading learning as evidenced by t-test with tcount = 4,4986> ttable = 2,1448.Keywords: CIRC, The Results of Learning Intensive Reading Abstrak Penelitian ini dilatarbelakangi karena rendahnya hasil belajar membaca intensif siswa yang salah satunya diakibatkan oleh proses pembelajaran yang kurang aktif, kreatif, dan inovatif. Penelitian ini bertujuan untuk mengetahui keefektifan model CIRC terhadap hasil belajar membaca intensif siswa kelas III SDN Bogorame Rembang. Penelitian ini adalah penelitian kuantitatif dengan desain Pre-Experimental dengan jenis One Group Pretest-Posstest. Teknik sampel yang digunakan adalah nonprobability sampling dengan jenis sampling jenuh. Populasi dalam penelitian ini adalah seluruh siswa kelas III SDN Bogorame Rembang tahun ajaran 2017/2018. Hasil dari penelitian menunjukkan bahwa model CIRC efektif terhadap hasil belajar membaca intensif siswa yang dibuktikan dengan uji t-test dengan perolehan thitung=4,4986 > ttabel=2,1448.Kata kunci : CIRC, Hasil Belajar Membaca Intensif